Plasma fluorination of carbon-based materials for imprint and molding lithographic applications - Schvartzman, M. (American Institute of Physics, 2008)
Diamondlike carbon nanoimprint templates are modified by exposure to a fluorocarbon-based plasma, yielding an ultrathin layer of a fluorocarbon material on the surface which has a very low surface energy with excellent antiwear properties. We demonstrate the use of these plasma fluorinated templates to pattern features with dimensions ∼20 nm and below. Furthermore, we show that this process is extendable to other carbon-based materials. Plasma fluorination can be applied directly to nanoimprint resists as well as to molds used to form elastomer stamps for microcontact printing and other applications requiring easy mold release.